2018
DOI: 10.3349/ymj.2018.59.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Flow Reserve in Non-Infarcted Myocardium Predicts Long-Term Clinical Outcomes in Patients Undergoing Percutaneous Coronary Intervention

Abstract: PurposeCoronary flow reserve (CFR) is recognized as an indicator of myocardial perfusion. The aim of this study was to assess the relationship between CFR in the non-infarcted myocardium and the incidence of major adverse cardiac events (MACEs).Materials and Methods100 consecutive patients with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) were enrolled in the present study, and divided into MACE and non-MACE groups according to the incidence of 12-month MACEs. Left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In previous studies, coronary flow reserve (CFR), which is one of the MCE quantitative parameters, was shown to correlate with MV and adverse ventricular remodeling after AMI [ 28 , 39 , 40 ]. A recent study [ 41 ] also demonstrated that CFR is an independent predictor of MACE in patients with AMI. Therefore, a large, prospective, multicenter study is necessary to definitively establish the MCE score index and other MCE quantitative parameters as long-term predictors of MACE after AMI.…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, coronary flow reserve (CFR), which is one of the MCE quantitative parameters, was shown to correlate with MV and adverse ventricular remodeling after AMI [ 28 , 39 , 40 ]. A recent study [ 41 ] also demonstrated that CFR is an independent predictor of MACE in patients with AMI. Therefore, a large, prospective, multicenter study is necessary to definitively establish the MCE score index and other MCE quantitative parameters as long-term predictors of MACE after AMI.…”
Section: Discussionmentioning
confidence: 93%